The The Implementation of Teachers' Pedagogical Competence in Elementary Schools - Zulkarnain, Zulkarnain; Adiputra, Sofwan; Amir, Arman (Kontribusia : Research Dissemination for Community Development, 2025)
Teachers play a crucial role in the education system, particularly in developing pedagogical competence to create effective learning. Pedagogical competence includes understanding student characteristics, applying learning theories, and managing a conducive classroom environment. However, in practice, many teachers still face challenges in optimally implementing pedagogical competence, especially in elementary schools within The X cluster area, Pardasuka Subdistrict, Pringsewu Regency. This study aims to examine teachers' understanding of pedagogical competence, identify its application in teaching, and reveal the challenges faced by teachers. The research method used is qualitative with a case study approach in five elementary schools in the area. Data collection was conducted through interviews, questionnaires, and documentation, which were then analyzed using the Miles and Huberman qualitative data analysis model. The results show that most teachers have a good understanding of pedagogical competence, but its implementation is still limited by constraints such as inadequate technological facilities, high administrative burdens, and a lack of continuous training. This study recommends reducing administrative burdens and enhancing sustainable professional development programs for teachers to optimize the application of pedagogical competence in teaching.